Linking top and subsoil types, alteration and degassing processes at Rotokawa geothermal field, New Zealand - Montanaro, Cristian; Ray, Lena; Cronin, Shane J.; Calibugan, Aimee; Rott, Stefanie; Bardsley, Candice; Scheu, Bettina (Frontiers in Earth Science, 2023)
Surface geothermal expressions such as mud pools, fumaroles, mineral deposits, collapse pits and hydrothermal eruption craters vary in scale and type, over space and time. Many are iconic tourist attractions (e.g. in Yellowstone, USA, or Wai-o-Tapu, NZ), or impact operating geothermal fields. The thermal area located south of the Rotokawa geothermal field (New Zealand), under Department of Conservation (DOC) management, includes a variety of major surface thermal features and widespread sulphur deposits in steam-heated zones. Sulphur mining has been a major activity at this site up until 1990, and thermal features have been superimposing the mined areas afterward. We combined field and laboratory methods to investigate such features and the soil characteristics to evaluate type and pattern of superposed hydrothermal alteration, and its effect on the degassing processes. We define three main domains and other scattered areas based on distinctive groups of thermal features, soil types and associated alteration. The spatial distribution of these domains and their features suggests that fluid circulation, alteration intensity, and degassing are strongly controlled by: i) field- and regional scale fault systems oriented ~NE-SW; ii) cross-cutting pre-historic hydrothermal craters; iii) heterogeneous properties of the Taupo Pumice ignimbrite deposit; and iv) recent mining activity leading to rapid formation of new thermal features and massive sulphur precipitation. Degassing and fluid circulation within top and subsoils is strongly affected by the dominant soil layer type, and in turn by their granulometry, texture and alteration state. Permeable pumice-dominated soil layers act as lateral fluid pathways, while low-permeability layers, silica sinters and sulphur-cemented soils inhibit surficial fluid degassing if not via fractures. Surface temperatures (<10 cm depth) range from 20 to >90°C, with the highest values only measured at active fumaroles, or collapsed structures. Colder (<30°C) top soil layers in sulphur-cemented ground, sinters and/or hardened clays, often mask heat flow from hotter (>50°C) subsoils. Our study of top and subsoils yields precious insights on surface expression variability, fluid-rock interaction processes, and sulphur deposition patterns within steam-heated zones. Processes at such scale may strongly influence the migration of thermal manifestations, gas outputs, as well as ground subsidence within geothermal environments.